Mood Investor Atas Pengumuman Pergantian Dewan Komisaris dan Dewan Direksi (Studi Pada PT Garuda Indonesia Tbk) - Versiandika Yudha Pratama; Farah Difa (Jurnal Manajemen Dirgantara, 2020)
This research aims to determine there are differences in average abnormal returns that occur before and after the announcement of the change of board (board of commissioners and board of directors) of PT. Garuda Indonesia, Tbk., which is on January 22nd, 2020. This research used event study for method and the data in this study are secondary data in the form of stock price data of PT. Garuda Indonesia, Tbk. The event window in this study for 11 (eleven) working days which is 5 (five) days before the event, 1 (one) day when the event occurs and 5 (five) days after the announcement of the change of the board of commissioners and board of directors. Meanwhile, the estimated period is set for 120 exchange days, namely at t-125 to t-6. Test conducted by paired sample t-test. The results of the paired sample t-test showed that there is no significant difference between the average abnormal returns before and after the announcement of the change of board (board of commissioners and board of directors) of PT. Garuda Indonesia, Tbk. It can be concluded that neither the market nor investors reacted to the announcement of the replacement of the board of commissioners and board of directors that occurred at PT Garuda Indonesia, Tbk